Biomimetic Magnetoliposomes as Oxaliplatin Nanocarriers: In Vitro Study for Potential Application in Colon Cancer - Beatriz Garcia-Pinel; Ylenia Jabalera; Raul Ortiz; Laura Cabeza; Concepción Jimenez-Lopez; Consolación Melguizo; Jose Prados (MDPI AG, 2020)
Current chemotherapy for colorectal cancer (CRC) includes the use of oxaliplatin (Oxa), a first-line cytotoxic drug which, in combination with irinotecan/5-fluorouracil or biologic agents, increases the survival rate of patients. However, the administration of this drug induces side effects that limit its application in patients, making it necessary to develop new tools for targeted chemotherapy. MamC-mediated biomimetic magnetic nanoparticles coupled with Oxa (Oxa-BMNPs) have been previously demonstrated to efficiently reduce the IC50 compared to that of soluble Oxa. However, their strong interaction with the macrophages revealed toxicity and possibility of aggregation. In this scenario, a further improvement of this nanoassembly was necessary. In the present study, Oxa-BMNPs nanoassemblies were enveloped in phosphatidylcholine unilamellar liposomes (both pegylated and non-pegylated). Our results demonstrate that the addition of both a lipid cover and further pegylation improves the biocompatibility and cellular uptake of the Oxa-BMNPs nanoassemblies without significantly reducing their cytotoxic activity in colon cancer cells. In particular, with the pegylated magnetoliposome nanoformulation (a) hemolysis was reduced from 5% to 2%, being now hematocompatibles, (b) red blood cell agglutination was reduced, (c) toxicity in white blood cells was eliminated. This study represents a truly stepforward in this area as describes the production of one of the very few existing nanoformulations that could be used for a local chemotherapy to treat CRC.